Bibliography of Ethiopian Semitic, Cushitic and Omotic Linguistics XXI: 2017 - Bulakh, Maria; Hummel, Susanne; Panini, Francesca (Aethiopica, 2018)
Bibliography of Ethiopian Semitic, Cushitic and Omotic Linguistics XXI: 2017